Peluang dan Tantangan Komunikasi Pemasaran pada Era Digital (Studi Kasus Pasar Kamu Desa Denai Lama, Pantai Labu, Deli Serdang) - Khairullah Khairullah; Nadiah Kusma (Jurnal Syntax Admiration, 2025)
This research aims to analyze the opportunities and challenges of marketing communication in the digital era, specifically KAMU Market in Denai Lama Village, Pantai Labu, Deli Serdang. The research methodology used is a case study of an interpretative nature, with data collection techniques including observation and literature study. The informants in this study consist of two managers and four visitors selected by purposive sampling. The data analysis technique in this research refers to the model by Matthew B. Miles and Michael Huberman (1984), namely: data reduction, data display, and conclusion. The theory used in this study is the dimensions found in e-WOM (Electronic Word of Mouth), specifically according to Goyette et al. (2010: 11), which includes intensity, valence of opinions, and content, particularly on Instagram @pasarkamu_. The results of this study indicate that The Management of Pasar KAMU has utilized Instagram for promotional purposes as an opportunity, focusing on content that incorporates elements of attractions, amenities, and accessibility in the context of tourism. Meanwhile, Pasar KAMU faces challenges in maximizing the potential of local influencers for promotional needs. Based on the dimensions of E-WoM, visitor engagement in receiving information about Pasar KAMU through social media is very high, accompanied by numerous positive comments and hashtags. However, accessibility-related content remains limited, and the Instagram account's visual presentation is still lacking in appeal.